2023
DOI: 10.20944/preprints202304.0194.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Boron Effect on Microstructure, Superplastic Behavior, and Mechanical Properties of Ti-4Al-3Mo-1V Alloy

Abstract: The microstructure evolution, superplasticity, and room temperature mechanical properties of Ti-4%Al-1%V-3%Mo alloys modified with 0.01-2 wt.% boron were investigated. Increasing the boron content from 0 to 0.1 wt.% effectively refined prior β-grains, reducing a mean grain size from ~700 µm to ~210 µm. Whiskers of the TiB phase with a size in a range of 0.7-2.9 µm were observed after solidification and thermomechanical processing. Alloys with 0.01-0.1 wt.% boron exhibited… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 55 publications
0
1
0
Order By: Relevance
“…The purpose of this study is to the influence of 0.5% to 2wt% Co on the microstructure and superplastic behavior of the Ti-4Al-3Mo-1V alloy to reduce the superplastic deformation temperature. In previous studies, it was found that the trace boron addition accelerates recrystallization and globularization of the microstructure [19] which provides a stable flow and reduces the flow stresses at the initial stage of superplastic deformation [20]. In this regard, the investigated alloys were also alloyed with 0.1wt% trace boron addition.…”
mentioning
confidence: 96%
“…The purpose of this study is to the influence of 0.5% to 2wt% Co on the microstructure and superplastic behavior of the Ti-4Al-3Mo-1V alloy to reduce the superplastic deformation temperature. In previous studies, it was found that the trace boron addition accelerates recrystallization and globularization of the microstructure [19] which provides a stable flow and reduces the flow stresses at the initial stage of superplastic deformation [20]. In this regard, the investigated alloys were also alloyed with 0.1wt% trace boron addition.…”
mentioning
confidence: 96%